Analisis Biaya Transportasi dan Biaya Persediaan pada PT Solid Global Solution D.K.I Jakarta - Nina Marlina; Bella Cantika; Hany Amanda Azahra; Rosyiana Dewi; Thanika Wahyuningsih (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
A good logistic system is really needed in a company to help in its development process. The aim of this research is to evaluate the logistic system and inventory cost at PT Solid Global Solution. This research uses qualitative methods with secondary data obtained from the observation and interview process. There are several problems found in the company which caused an increase in shortage costs and holding costs. These findings provide suggestions for improvements that can be implemented in order to minimize inventory costs incurred.